2009
DOI: 10.1007/s12633-009-9004-4
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-mediated Synthesis of Silsesquioxanes

Abstract: In an initial report we demonstrated that some serine proteases were suitable candidates for the hydrolysis and condensation of tetraethoxysilane and phenyltrimethoxysilane under solvent-free conditions. Using trypsin as a model enzyme, we have demonstrated the generality of this method by expanding the number of available silicon-based substrates that can be processed by the enzyme, as well as including pepsin to demonstrate that this phenomenon is not exclusive to a single family of enzymes. A series of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
(132 reference statements)
1
18
0
Order By: Relevance
“…The data also suggested that other lipase and protease enzymes promoted the formation of siloxane bonds by condensation under the same conditions. Similarly, Zelisko reported that certain proteases could mediate the sol-gel processing of TEOS and phenyltrimethoxysilane [14] and other organosilicon substrates [15]. In addition we demonstrated that certain enzymes were able to accelerate silica deposition with resultant formation of silicaenzyme composites while retaining enzymatic activity [16].…”
Section: Introductionsupporting
confidence: 69%
“…The data also suggested that other lipase and protease enzymes promoted the formation of siloxane bonds by condensation under the same conditions. Similarly, Zelisko reported that certain proteases could mediate the sol-gel processing of TEOS and phenyltrimethoxysilane [14] and other organosilicon substrates [15]. In addition we demonstrated that certain enzymes were able to accelerate silica deposition with resultant formation of silicaenzyme composites while retaining enzymatic activity [16].…”
Section: Introductionsupporting
confidence: 69%
“…Enzyme inhibition experiments with trypsin suggested that hydrolysis and condensation of phenyltrimethoxysilane could not be realized when the active site was blocked with a Kunitz type inhibitor. The results from several 29 Si NMR experiments demonstrated that trypsin, and additionally pepsin, were suitable candidates for mediating the sol-gel processing of several alkoxysilanes to form monolithic organosilica [97]. Fig.…”
Section: Sol-gel Processing Of Rsi(or')mentioning
confidence: 97%
“…The forefront of enzyme-silica interactions has been dominated by silicatein, however, other enzymes have recently been shown to mediate similar transformations [96][97][98][99]. Frampton et al have recently demonstrated that a variety of proteolytic enzymes could be used to mediate the formation of bio-hybrid organosilica monoliths under ambient conditions [96,97].…”
Section: Sol-gel Processing Of Rsi(or')mentioning
confidence: 99%
See 1 more Smart Citation
“…[67] Depending on the enzymes being utilized, rate enhancements of 11-155 times that of the enzyme-free controlsw ere observed. By performing 29 Si NMR reactions in D 2 O, the relative proportion of phenyltrimethoxysilane, phenylsilanetriol, dimerization products, and oligomerization productsf or the trypsin-catalyzed reactions werev isualized ( Figure 12).…”
Section: Small-molecule Silane Systemsmentioning
confidence: 99%